Visualisasi Penelitian Tentang Tembang Macapat dari Tahun 1981 – 2021 : Analisis Bibliometrik - Oka Irmade; Winarto Winarto (Gelar : Jurnal Seni Budaya, 2021)
The macapat song in Indonesia has been widely studied and has become an interesting topic for international analysis. The purpose of this study is to provide an overview of the extent to which the tembang macapat has been researched and published in reputable international journals. This study analyzes the literature from 1981 to 2021, identifies the publications each year, the number of articles and their authors, the most researched topics, and how interested they are in those topics. The data came from the Scopus database which was analyzed by the bibliometric method. The results of this study found articles about tembang macapat were published in Scopus indexed journals and topics related to macapat, namely ketoprak, cross-cultural perspectives, social change perspectives, Javanese, writing, and a few others. From the results of this visualization, it is necessary to increase the publication of research results in the international arena so that everything contained in the macapat song can also be known not only in Indonesia.